Early Pregnancy Diagnosis in Bovines: Current Status and Future Directions - Ashok K. Balhara; Meenakshi Gupta; Surender Singh; Ashok K. Mohanty; Inderjeet Singh (The Scientific World Journal)
An early and accurate diagnosis of reproductive dysfunctions or aberrations is crucial to better reproductive management in livestock. High reproductive efficiency is a prerequisite for high life-time production in dairy animals. Early pregnancy diagnosis is key to shorten the calving interval through early identification of open animals and their timely treatment and rebreeding so as to maintain a postpartum barren interval close to 60 days. A buffalo, the most important dairy animal in the Indian subcontinent, is known for problems related to high calving interval, late puberty, and high incidence of anestrus. Lack of reliable cow-side early pregnancy diagnosis methods further aggravates the situation. Several methods of pregnancy diagnosis are being practiced in bovine species, yet none qualifies as the ideal pregnancy diagnosis method due to the inherent limitations of sensitivity, accuracy, specificity, speed, and ease of performing the test. The advancement of molecular techniques like proteomics and their applications in animal research has given a new hope to look for pregnancy biomarker molecules in these animals. This review attempts to examine common pregnancy diagnosis methods available for dairy animals, while assessing the usefulness of the modern technologies in detecting novel pregnancy markers and designing future strategies for research in this area.